ERYSIPELAS PADA HEWAN DAN ERYSIPELOID PADA MANUSIA (SEBUAH ZOONOSIS) - Devi Y. J. A. Moenek (Politeknik Pertanian Negeri Kupang, 2009)
Animal Erysipelas dan Human Erysipeloid ( a Zoonosis). Erysipelas is a type of zoonosis that may be infects on all continent among many species of domestid and wild mammal and birds. The etiologic agent is E. rhusiopathiae. These agent can multiply in an apparently healthy carrier under stress, and can cause disease and contaminate environment. Man is infected through wounds and skin abrasions. The infection is contracted by handling animals and animal products, including fish. Keywords : erysipelas, erysipeloid, zoonosis